Biology of Coccinella transversalis Muls. (Coloeptera: Coccinellidae) - Balbarino, Brenda C.; Ceniza, Ma. Juliet C. (Annals of Tropical Research, 2005)
The biology of Coccinella transversalis reared on black bean aphid, Aphis craccivora was studied in the laboratory. The beetle passed through the egg, 4 larval instars, pupa and adult stages. The eggs were spindle-shaped and had an incubation of 2-3 days with an average of 2.85 days. The larvae which were typically black with orange bands or tinge on the methoracic region and some part of the abdomen has a total development period of about 6-9 days, with an average of 7.27 days. The pupal period lasted for about 3-4 days, or 3.38 days on the average. The total development period from egg to adult emergence took about 13-15 days. The adults which were typically red orange with black inverted v markings on the elytra lived for an average of 51.34 days. The female laid an average of 1000 eggs under laboratory condition.